Legal Protection for Victims of Cyberbullying on Social Media: A Human Rights Perspective - William Wun; Siska Aprelyani (Journal of Law and Humanities Review, 2025)
Cyberbullying on social media has become a growing legal and human rights concern due to its potential to harm victims’ dignity, privacy, psychological well-being, and freedom of expression. This study aims to examine legal protection for cyberbullying victims from a human rights perspective, with a comparative focus on Indonesia and France. This research employs a Systematic Literature Review (SLR) method by identifying, selecting, evaluating, and analyzing relevant scientific literature and legal regulations concerning cyberbullying and victim protection. The findings indicate that Indonesia provides legal protection through several instruments, including the Electronic Information and Transactions Law, the Human Rights Law, the Personal Data Protection Law, and regulations concerning the protection of witnesses and victims. France provides protection through the Penal Code, particularly provisions concerning moral harassment and cyber-harassment, as well as mechanisms for reporting, content removal, victim assistance, and platform responsibility. From a human rights perspective, both countries recognize the importance of protecting victims’ dignity, privacy, security, and mental well-being while maintaining a balance with freedom of expression. The study concludes that effective cyberbullying protection requires not only legal sanctions but also prevention, accessible reporting mechanisms, digital literacy, platform accountability, and comprehensive victim support.